Sexual and reproductive health needs of adolescents growing with perinatally acquired HIV at Mzuzu Central Hospital - Ngwira, Thom George (2021)
Adolescents with perinatally acquired HIV are growing up to adulthood. Data from the Rainbow Clinic in 2015 indicated that there were 94 adolescents growing up with perinatally acquired HIV accessing services at the hospital. Provision of the services at the Clinic is ill-equipped to address the specific age-appropriate sexual and reproductive health needs of adolescents growing up with HIV. This is complicated in adolescents with perinatally acquired HIV who have both psychological and physiological problems. This study sets up to explore the SRH needs for adolescents growing up with perinatally acquired HIV from the service providers and the adolescents themselves. This study was qualitative in nature that used an exploratory design to understand the SRH needs for adolescents growing up with perinatally acquired HIV. Qualitative data was collected from seventeen adolescents growing up with perinatally acquired HIV and five service providers using semi structured interview guides and focus group discussion for a period of approximately four weeks. The thematic content analysis was used to manage and analyse data manually. Study results revealed that a generalised lack of knowledge on sexual and reproductive needs among adolescents growing up with HIV accessing services at the clinic. The clinic also is not yet integrated to provide a full range of sexual and reproductive health services together with HIV services. Access to information on SRH is limited as adolescents are not adequately provided with this information. However adolescents suggest practical strategies to improve SRH service delivery. Adolescents growing up with HIV need age appropriate services that are comprehensive as to assist them with the challenges they face as they grow up with HIV in order to improve their quality of life. The need for adolescents to access services under one roof ensures that adolescents living with HIV can have an easy access to both HIV and SRH services rather than HIV treatment and care alone.